Системы управления умным домом - Ярова, Ю. Д.; Мерзликин, А. А. (ХНУРЕ, 2018)
This report examines the management system of a smart house. Control panels are considered: push-button, touch, and others. Types of control systems are presented. The pros and cons of each of them are considered. It is concluded that the wireless decentralized type is the most optimal and less labor-intensive for smart home equipment. And management is best done through the cloud service.
Keywords: системы управления; умный дом; виды панелей; системы автоматизации